Correlation of Knowledge Level and Stroke Prevention Efforts in Hypertension Patients in the Working Area of Samadua Health Center, South Aceh Regency - Yenni Sasmita; Fathimi; Desriati Devi; Hilma Yasni; Rasima (Postgraduate, University of Mataram, 2025)
The purpose of this study was to find out how the level of knowledge of hypertension patients is related to stroke prevention efforts in the working area of the Samadua Health Center, South Aceh district. This study was a type of correlative descriptive research with a cross-sectional approach with chi-square test. Sampling was done using the purposive sampling method by distributing a questionnaire as an instrument and the analysis was carried out with the chi square test. The sample in this study is 50 hypertensive patients who are outpatients in the working area of the Samadua Health Center, South Aceh Regency. The results showed that (p=0.001), meaning that there was a relationship between the knowledge of hypertension patients and efforts to prevent stroke events. The conclusion shows that there is a relationship between the knowledge of hypertension patients and efforts to prevent stroke incidence. Respondents should focus more on their health, particularly during early exams, and broaden their understanding of stroke prevention caused by excessive blood pressure.